Pengembangan Website Company Profile Dinamis Berbasis CMS pada PT Dhiatek Indo Jaya - Elga Legianti; Diaz Fabian Luthfi; Ivana Rubby Abigael; Maulana Ardhiansyah (CV. Shofanah Media Berkah, 2026)
This research aims to transform the company profile website of PT Dhiatek Indo Jaya from a static system into a dynamic one, in order to improve the effectiveness of service information dissemination and user interaction. The main problem with the previous system was an architecture that made real-time content updates difficult and the absence of two-way communication features. The system development method used is the Waterfall model, covering requirements analysis, system design using Unified Modeling Language (UML) diagrams, program implementation, and system testing. The technologies implemented include the Laravel framework and the MySQL database management system. This research produced a company profile website integrated with a Content Management System (CMS) and an interactive contact form. Evaluation results show that the implementation of the CMS successfully eliminated dependence on manual source-code modification, allowing portfolio information to be updated independently and efficiently by non-technical staff. Functional testing using the Black Box Testing method confirmed that all features, from login authentication to content management, operate validly according to the company's business requirement specifications. It can be concluded that this dynamic website development is able to strengthen the professional image of PT Dhiatek Indo Jaya in the digital market.